Automatic counting method using fast radial symmetry transform - Boonyarat Viriyasaksathian (2018)
This paper proposes an automatic but simple counting method for counting the symmetric objects. In stead of using the classical thresholding method to segment the area of interest, fast radial symmetry transform is employed to segment the symmetric areas which are also the areas of interest. Simulation results show that the proposed counting method yields 100% counting accuracy in pills counting even though the pills are overlapped and of different sizes. © 2008 IEEE.